Numerical investigations of the aerodynamics and handling qualities of a helicopter flying across a wind turbine wake - Visingardi, A.; Pavel, M.D. (My University, 2018)
The present paper illustrates the outcomes of a research activity carried out by CIRA and the Delft University of Technology in the framework of the GARTEUR HC/AG-23 action group. This activity has been aimed at investigating, from the aerodynamic and handling qualities point of view, the problem of a Bo105 helicopter rotor crossing, in low-speed level flight, the wake of an NREL 5MW wind turbine (WT), in the presence of atmospheric boundary layer (ABL). A crossing flight path orthogonal to the WT axis, and located two WT rotor diameters downstream to the WT disk, has been selected. Three different flight altitudes, with respect to the WT hub, and two flight directions, L2R and R2L, have been investigated. The aerodynamic simulations have been carried out by using a BEM methodology and by applying a decoupled interactional procedure specifically conceived for the purpose. The rotor blades have been assumed fully rigid. The simulations have shown that the encounter of a uniform side wind or a WT wake with a helicopter rotor, locally alters the velocities acting on the helicopter rotor blades, in magnitude and/or direction, because of the WT axial and radial changes in velocity deficit; the presence of the WT blade tip vortices; the presence of the ABL; the WT wake swirl. These velocities modify the helicopter rotor blade sectional effective angles of attack, which, in turn, change the blade loads, generate flapping angles and alter the rotor forces and moments. Compared to the flight inside a uniform side wind, the crossing of a WT wake produces important rotor rolling and pitching moments, the thrust increases while the torque decreases. The flight altitude has only moderate effects. Regarding the handling qualities, the paper has considered the ADS-33 pitch and roll attitude quickness parameters and has shown that when the WT wake approaches the helicopter from left to right (L2R) this results in an increase in the quickness that pilot needs to command. The analysis of the results has concluded that, for a WT rotor and helicopter rotor both counter-clockwise rotating, a pilot experiences a greater workload during the L2R crossing of the WT wake, but also that this situation is transient in nature and the pilot needs to command it only momentarily.